Interdisciplinary Mathematics Education The State of the Art and Beyond - Doig, Brian; Williams, Julian; Swanson, David; Borromeo Ferri, Rita; Drake, Pat (ICME-13 Monographs, 2019)
This open access book is the first major publication on the topic of "Interdisciplinary Mathematics Education" and arose from the work of the first International Topic Study Group of the same name at the ICME-13 conference in Hamburg in 2016. It offers extensive theoretical insights, empirical research, and practitioner accounts of interdisciplinary mathematics work in STEM and beyond (e.g. in music and the arts). Scholars and practitioners from four continents contributed to this comprehensive book, and present studies on: the conceptualizations of interdisciplinarity; implementation cases at schools and tertiary institutions; teacher education; and implications for policy and practice. Each chapter, and the book itself, closes with an assessment of the most significant aspects that those involved in policy and practice, as well as future researchers, should take into account.